2021
DOI: 10.1111/1365-2664.14089
|View full text |Cite
|
Sign up to set email alerts
|

The sound of recovery: Coral reef restoration success is detectable in the soundscape

Abstract: 1. Pantropical degradation of coral reefs is prompting considerable investment in their active restoration. However, current measures of restoration success are based largely on coral cover, which does not fully reflect ecosystem function or reef health.2. Soundscapes are an important aspect of reef health; loud and diverse soundscapes guide the recruitment of reef organisms, but this process is compromised when degradation denudes soundscapes. As such, acoustic recovery is a functionally important component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Thus, further investigation is needed to understand the relative importance of physical drivers on soundscape variation in snapping-shrimp dominated seas. Interacting direct and indirect effects of climate changes and snapping shrimp habitat degradation (e.g., coral bleaching, sponge host die-off) on soundscape variation should also be considered (Butler et al, 2016;Butler et al, 2017), particularly since snapping sounds strongly influence commonly used passive acoustic monitoring metrics of habitat health (Bohnenstiehl et al, 2018;Elise et al, 2019) and have been suggested as indicators of "healthy" soundscapes or habitat restoration success (Butler et al, 2021;Lamont et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, further investigation is needed to understand the relative importance of physical drivers on soundscape variation in snapping-shrimp dominated seas. Interacting direct and indirect effects of climate changes and snapping shrimp habitat degradation (e.g., coral bleaching, sponge host die-off) on soundscape variation should also be considered (Butler et al, 2016;Butler et al, 2017), particularly since snapping sounds strongly influence commonly used passive acoustic monitoring metrics of habitat health (Bohnenstiehl et al, 2018;Elise et al, 2019) and have been suggested as indicators of "healthy" soundscapes or habitat restoration success (Butler et al, 2021;Lamont et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial changes in natural soundscapes have occurred due to increases in human use (Slabbekoorn et al, 2010;Butler et al, 2016;Buxton et al, 2017;Duarte et al, 2021), and a recent body of research has focused on anthropogenic noise and its detrimental impacts on organism physiology and behavior (e.g., Luczkovich and Sprague, 2008;de Soto et al, 2013;Hawkins and Popper, 2017;Jones et al, 2020). Increasing attention is also being given to soundscape measurement and analysis as an approach to monitor the impacts of human disturbance and climate change on biodiversity (Gage and Axel, 2014;Krause and Farina, 2016;Lamont et al, 2022). Far less is known about climate-driven changes to the soundscape and the biological drivers of those potential alterations, particularly for acoustically-rich ocean habitats.…”
Section: Introductionmentioning
confidence: 99%
“…These ‘muted‐scapes’ carry less navigational information to dispersing organisms (Williams et al, 2021) in search for adult habitat. Hence, coastal restoration efforts that seek to restore habitat‐forming species and their ecosystem functions, which in turn revive these soundscapes (Lamont et al, 2021), may have low capacity for restoration where recruitment is limited. The most soniferous producers of biological noise in marine habitats are snapping shrimp (Johnson et al, 1947).…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial that marine soundscape studies continue to be developed and pursued, in order to establish baselines for healthy ecosystems and/or document recovery following management actions (Lamont et al, 2021). With the rapid innovation of technology, especially data storage and declining cost of equipment, marine soundscape research is rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%